Hepatocellular carcinoma-targeted effect of configurations and groups of glycyrrhetinic acid by evaluation of its derivative-modified liposomes - Sun, Yuqi (Int J Nanomedicine, 2018)
BACKGROUND: There are abundant glycyrrhetinic acid (GA) receptors on the cellular membrane of hepatocytes and hepatocellular carcinoma (HCC) cells. The receptor binding effect might be related to the structure of the guiding molecule. GA exists in two stereoisomers with C3-hydroxyl and C11-carbonyl active groups. PURPOSE: The objective of this study was to investigate the relationship between the HCC-targeted effect and the configurations and groups of GA. METHODS AND RESULTS: Different GA derivatives (18β-GA, 18α-GA, 3-acetyl-18β-GA [3-Ace-GA] and 11-deoxy-18β-GA [11-Deo-GA]) were used to investigate the targeting effect of GA’s configurations and groups on HCC cells. The EC(50) values of competition to binding sites and the ratio of specific binding in HepG2 cells showed that 18β-GA and 3-Ace-GA demonstrated significant competitive effect with fluorescein isothiocyanate (FITC)-labeled GA. Then, the GA derivatives were distearoyl-phosphatidylethanolamine (DSPE)-PEGylated. 18β-GA-, 18α-GA-, 3-Ace-GA-and 11-Deo-GA-modified liposomes were prepared and characterized by size, zeta potential, encapsulation efficiency, loading capacity, leakage and membrane stability. Evaluation on the cellular location in vitro and tumor targeting in vivo was carried out. Compared to common long-circulation liposome (PEG-Lip), more 18β-GA- and 3-Ace-GA-modified liposomes aggregated around HepG2 cells in vitro in short time and transferred into HCC tumors in vivo for a longer time. CONCLUSION: The β-configuration hydrogen atom on C18 position of GA played the most important role on the targeting effect. C11-carbonyl and C3-hydroxy groups of GA have certain and little influence on targeting action to HCC, respectively. In general, GA might be a promising targeting molecule for the research on liver diseases and hepatoma therapy.